Digital Financial Inclusion and Implications for Developing Countries Economic Growth - Yaqin, Misbahol; Safuan, Sugiharso (Universitas Airlangga, 2023)
This study aims to develop a model to measure financial inclusion by incorporating the evolution of digital finance and identifying its relationship with GDP growth in emerging nations. Data used are from 51 developing countries in 2014 and 2017. Principal component analysis (PCA) was used to create the Digital Financial Inclusion Index. The fixed effects model (FEM) is used to estimate the association between the inclusion of digital finances and economic growth. According to the study, metrics of digital financial inclusion in emerging nations are in the middle. Compared to other research, the financial inclusion indicator in this study strengthens it. The study discovered that the inclusion of digital finance enhances GDP growth in developing nations after testing the influence of digital financial inclusion on GDP growth in developing countries.